Biodiversity patterns of butterflies and moths on Mount Cameroon - Maicher, Vincent (Jihočeská univerzita, 2019)
Biodiversity patterns of butterflies and moths are investigated on the southwestern slope of Mount Cameroon, the only continuous elevational gradient of near-pristine forests in the Afrotropics. Three distinct seasons between 2014 and 2017 are sampled by two standardised methodologies (i.e., bait-trapping and manual catching of selected groups of moths at light). First, the effects of seasonality and forest habitat associations on butterflies and moths are investigated in the lowland rainforest. Then, the impacts of elephant-made natural disturbances on tree, butterfly, and moth diversities at mid-elevations is evaluated. The thesis also includes faunistic records of species never reported from the area, combining them with life history notes on selected taxa and species description of nine new species of Alucita. Finally, the last chapter focuses on the biodiversity of birds, trees, and butterflies in the last large patch of coastal forest of the studied area, and discusses its current conservation status.
Biodiversity patterns of butterflies and moths on Mount Cameroon
Keywords: biodiverity; butterflies; moths; mount Cameroon; biodiverity; butterflies; moths; mount Cameroon